Implementasi Absensi Elektronik Dalam Membentuk Budaya Kerja Pegawai Negeri Sipil Pada Dinas Pekerjaan Umum, Penataan Ruang, Perumahan dan Kawasan Permukiman Kabupaten Tabanan - Gusti Ayu Made Manik Prahandari; I Ketut Suardana (Jurnal Widya Mahavira, 2025)
This study examines the implementation of electronic attendance in shaping the work culture of Civil Servants (PNS) at the Public Works, Spatial Planning, Housing and Settlement Areas Office (PUPRPKP) of Tabanan Regency. The purpose of the study is to understand the impact of the electronic attendance system on the formation of civil servants' work culture. The research uses a qualitative approach with observation, interview, and documentation techniques, and utilizes primary and secondary data. The theoretical foundation uses the theory of decision making Xing (2015) and the behavioral theory of Notoatmodjo (2017). The results of the study show that online presence has a positive impact on the level of discipline of civil servants of the Tabanan Regency PUPRPKP Office. This is evident from the improvement in the performance of agencies that achieved a B rating in the Government Agency Performance Report (LKJIP). The implementation of this system has succeeded in eliminating the practice of manipulating absences such as depositing or resuming absences that previously occurred in the manual system. Online attendance is also a requirement to get Employee Income Supplement (TPP). Even though there are still employees who are late, they still show dedication in carrying out their responsibilities to provide excellent service to the community.